Implementasi Kebijakan Penerimaan Peserta Didik Baru (PPDB) di SMA Negeri 1 Abiansemal Kabupaten Badung - Yuda Putra, I Gst Ngr Herry; Yasintha, Putu Nomy; Wismayanti, Kadek Wiwin Dwi (CITIZEN CHARTER; Vol 1 No 2 (2019), 2020)
ABSTRACT This research aims to describe The implementation of PPDB zoning in Bali province especially in SMA N 1 Abiansemal . The method used in this research is qualitative method with descriptive type with data collection techniques in the form of observation, interviews, and documentation. Analysis using policy implementation theory according to Van Meter and Van Horn with indicators of size and objectives of policies, resources, characteristics of implementing agents, disposition of executives, communication between organizations and implementing activities  and social and political economic environment.Based on the results of the analysis above, the conclusion of the results of this research is the implementation of PPDB zoning in Bali province, especially in SMA N 1 Abiansemal has succeeded in the efforts to tell the access and quality of education. Keywords: policy implementation, PPDB, zoning.